2002
DOI: 10.1095/biolreprod66.4.924
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Programming: Prenatal Androgen Disrupts Positive Feedback Actions of Estradiol but Does Not Affect Timing of Puberty in Female Sheep1

Abstract: We studied the impact of prenatal androgen exposure on the timing of onset of puberty, maintenance of cyclicity in the first breeding season, and the LH surge mechanism in female sheep. Pregnant sheep were injected with testosterone propionate (100 mg i.m.) twice each week from Day 30 to Day 90 (D30-90) or from Day 60 to Day 90 (D60-90) of gestation (term = 147 days). Concentrations of plasma progesterone and gonadotropins were measured in blood samples collected twice each week from control (n = 10), D60-90 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 38 publications
12
98
3
3
Order By: Relevance
“…Ovaries from androgenized animals were larger and contained either an increased number of large antral follicles, follicular cysts (with a thin or absent membrana granulosa) or an increased stroma (or both; Sharma et al 2002). In one case, the ovary of an androgenized animal was almost completely occupied by a large follicular cyst.…”
Section: Ovarian Morphologymentioning
confidence: 99%
“…Ovaries from androgenized animals were larger and contained either an increased number of large antral follicles, follicular cysts (with a thin or absent membrana granulosa) or an increased stroma (or both; Sharma et al 2002). In one case, the ovary of an androgenized animal was almost completely occupied by a large follicular cyst.…”
Section: Ovarian Morphologymentioning
confidence: 99%
“…In normal control females, the tonic increase in LH secretion begins at 30 weeks of age in contrast to the earlier initiation of tonic LH secretion, which is usually displayed at 10 weeks of age in T-females (Wood et al, 1991;Wood et al, 1995). However, in other studies of prenatally androgenized females with intact ovaries, females unexpectedly did not show the early increase in tonic LH secretion leading to puberty but rather puberty was achieved at the same time as controls (Sharma et al, 2002;Birch et al, 2003). Our results provide additional support to the findings of Sharma and colleagues (2002), since we observed that the onset of puberty in two androgenized females was almost coincident with two control females.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, it has been established that the prenatal androgen exposure (PAE) in females born to testosterone (T)-treated sheep or monkey mothers is associated with growth retardation, infertility, obesity and insulin resistance during adulthood, although some of these characteristics could be expressed early in the extra-uterine life Recabarren et al, 2003;2005;Birch et al, 2003). Ovarian acyclicity, ovarian follicular disruption in prenatally T-treated sheep manifested as a reduction in number of 2-mm follicles, an increase in the size of large follicles and prolonged persistence, associated with hypergonadotropism comparable to those seen in PCOS, have been observed as well, all of which may be initiated early during post-natal life or during fetal development (Sharma et al, 2002;Birch et al, 2003;West et al, 2001;Padmanabhan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, la administración de dihidrotestosterona a la madre permite diferenciar el efecto de los andrógenos aromatizables de los no aromatizables, estableciéndose que la aromatización es necesaria para prevenir el alza preovulatoria de la hormona liberadora de gonadotropinas (GnRH), una característica de la hembra 33,34 .…”
Section: A R T í C U L Ounclassified